Cultural Cultural Value Representation on the Lexicon of Magelang Mantyaseh Batik: Ethnolinguistics Study - Astuty, Astuty; Sukarno, Sukarno; Wahyono, Hari (Universitas Negeri Semarang, 2020)
Mantyasih Batik is a valuable historical artifact. There are many facts about Mantyasih Batik viewed from language and cultural aspects. Mantyasih Batik is a manifestation of education and cultural value in society. In this study, Mantyasih Batik is an object of qualitative research in terms of language and culture. This research is aimed: (1) to identify the Mantyasih Batik lexicon based on the tools, materials, process, and motifs, (2) to identify the Mantyasih Batik lexicon forms based on the tools, materials, process, and motifs, and (3) to reveal the cultural value reflected on the Mantyasih Batik motifs. The data were collected through a survey, literature study, and in-depth interview with the initiator of Mantyasih Batik, crafters, cultural practitioner, and the elders of Mantyasih village. This research applied an ethnolinguistics approach to analyze the correlation of language and culture implemented in Mantyasih Batik. The results show that there are 7 lexicons found in terms of the tool, 3 lexicons in terms of the material, 7 lexicons in terms of the process, and 6 lexicons in terms of the motif. The lexicons are in the forms of word and phrase. The cultural value in the forms of lumpang batu and bunga mawar (rose) reflected the ritual offerings in the traditional ceremony of Manusuk. The sima of the Mataram Hindu Kingdom is associated with the establishment of the Magelang City, while kembang suket symbolizes fertility.